Higher prevalence of stunting and poor growth outcomes in HIV-exposed uninfected than HIV-unexposed infants in Kenya. (15th March 2022) - Neary, Jillian; Langat, Agnes; Singa, Benson; Kinuthia, John; Itindi, Janet; Nyaboe, Edward; Ng'anga', Lucy W.; Katana, Abraham; John-Stewart, Grace C.; McGrath, Christine J.
Abstract : Background: With the growing population of HIV-exposed uninfected (HEU) children globally, it is important to determine population-level growth differences between HEU and HIV-unexposed uninfected (HUU) children. Methods: We analyzed data from a population-level survey enrolling mother–infant pairs attending 6-week and 9-month immunizations in 140 clinics across Kenya. Weight-for-age (WAZ), length-for-age (LAZ), head circumference-for-age (HCAZ) z -scores and underweight (WAZ < −2), stunting (LAZ < −2), and microcephaly (HCAZ < −2), were compared between HEU and HUU. Correlates of growth faltering and poor growth were assessed using generalized Poisson and linear regression models. Results: Among 2457 infants, 456 (19%) were HEU. Among mothers living with HIV, 64% received antiretroviral therapy (ART) and 22% were on antiretroviral prophylaxis during pregnancy. At 9 months, 72% of HEU and 98% of HUU were breastfeeding. At 6 weeks, HEU had lower mean WAZ (−0.41 vs. −0.09; P < 0.001) and LAZ (−0.99 vs. −0.31; P = 0.001) than HUU. Stunting was higher in HEU than HUU at 6 weeks (34% vs. 18%, P < 0.001) and 9 months (20% vs. 10%, P < 0.001). In multivariable analyses, HEU had lower mean LAZ at 6 weeks (−0.67, 95% confidence interval [CI]: −1.07, −0.26) and 9 months (−0.57, 95% CI: −0.92, −0.21) and HEU had higher stunting prevalence (week-6 adjusted prevalence ratio [aPR]: 1.88, 95% CI: 1.35, 2.63; month-9 aPR: 2.10, 95% CI: 1.41, 3.13). HEU had lower mean head circumference (−0.49, 95% CI: −0.91, −0.07) and higher prevalence of microcephaly (aPR: 2.21, 95% CI: 1.11, 4.41) at 9 months. Conclusion: Despite high maternal ART coverage, HEU had poorer growth than HUU in this large population-level comparison. Optimizing breastfeeding practices in HEU may be useful to improve growth.